Realization of a 594 Wh kg−1 Lithium‐Metal Battery Using a Lithium‐Free V2O5 Cathode with Enhanced Performances by Nanoarchitecturing. Issue 1 (10th November 2022) - Sim, Kiyeon; Kwon, JunHwa; Lee, Seungmin; Song, Hayong; Cho, Ki‐Yeop; Kim, Subin; Eom, KwangSup
Abstract: To realize a high‐energy lithium metal battery (LMB) using a high‐capacity Li‐free cathode, in this work, nanoplate‐stacked V2 O5 with dominantly exposed (010) facets and a relatively short [010] length is proposed to be used as a cathode. The V2 O5 nanostructure can be fabricated via a modified hydrothermal method, including a Li + crystallization inhibitor, followed by heat treatment. In particular, the enlargement of the favorable Li + diffusion pathway in the [010] direction and the formation of a robust hierarchical nanoplate‐stacked structure in the modified V2 O5 improves the electrochemical kinetics and stability; as a result, the nanoplate‐stacked V2 O5 electrode exhibits a higher capacity and rate performance (258 mAh g −1 at 50 mA g −1 [0.17 C], 140 mAh g −1 at 1 A g −1 [3.4 C]) and cycling capability (79% capacity retention after 100 cycles at 0.5 C) compared to the previously reported V2 O5 nanobelt electrode. Notably, the LMB composed of Li//nanoplate‐stacked V2 O5 full‐cells shows high specific energy densities of 594.1 and 296.2 Wh kg −1 at 0.1 and 1.0 C, respectively, and a high Coulombic efficiency of 99.6% during 50 cycles. Abstract : A nanoplate‐stacked V2 O5 (VO) cathode material for high‐energy lithium metal battery (LMB) is developed by controlling the crystal growth to be favorable for Li + diffusion. Due to the enhanced electrochemical kinetics and stability compared to the nanobelt VO, LMB adopting nanoplate‐stacked VO shows high specific energies of 594.1 and 296.2 Wh kg −1 at 0.1 and 1 C, respectively.